The Contribution of Self-Concept, Independence, and Creativity to the Literacy Competency of the Fourth-Grade Elementary School Students - Dewi, I Gusti Ayu Wira Puspita; Astawan, I Gede; Julaeha, Siti (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
This research is quantitative with an ex-post-facto design. It aims to determine the contribution of self-concept, independence, and creativity to the literacy competence of fourth-grade elementary school students in Gugus IV, Abiansemal District. The population of this study was 131 students, while the sample was 97 students, and was determined by using the Proportional Stratified Random Sampling Technique. Data were collected by using a questionnaire and a test. All in all, the results showed: 1) there was a significant contribution of self-concept to students' literacy competence with a contribution of 51.9% and an effective contribution of 25.38%, 2) there was a significant contribution of independence to competence student literacy with a contribution of 43.5% and contribution of 23.51%, 3) there was a significant contribution of creativity to students' literacy competence with a contribution of 41.5% and contribution of 20%. 4) Simultaneously, there was a significant contribution of self-concept, independence, and creativity to students' literacy competence with a contribution of 68.9%.